EFFECTIVENESS OF SOME NON PATHOGENIC ENDOPHYTIC BACTERIA NUTMEG ON VIABILITY OF ORIGIN PLANT SEED RICE (Oryza sativa L) - Saiful Mahdi; Danar Hadisugelar; Dianawati; Afriyani; Safrizal (RADJA PUBLIKA, 2025)
This study aimed to determine the effectiveness of several non-pathogenic endophytic bacteria isolated from nutmeg plants on the viability of rice seeds. The experimental design used was a non-factorial completely randomized design (CRD) with three replications. The study included 14 endophytic bacterial treatments and one control. The research was conducted at the Biological Control Laboratory, Plant Protection Study Program, Faculty of Agriculture, Syiah Kuala University, Banda Aceh, from August 2023 to September 2023. The results showed that the application of non-pathogenic endophytic bacteria from nutmeg had a highly significant effect on rice seed viability, particularly on growth potential and germination. The highest seed viability was observed in the treatment with the bacterial isolate S - S AG 1 I. Endophytic bacterial isolates from nutmeg plants were proven to enhance the viability of Ciherang rice seeds, especially in terms of growth potential and germination. The isolate S - S AG 1 I produced the best results, with a growth potential of 84.4% and germination rate of 77.8%